Downstream Migration of Burbot (Lota lota) Larvae in the Subglacial Period - Chemagin Andrey; Volosnikov Gleb; Drabovich Yuri (BIO Web of Conferences)
The research was carried out in the Ob-Irtysh basin on the Irtysh River. The studied section of the river is located in Western Siberia in the Tyumen region. The dynamics of the downstream migration of burbot larvae were assessed in the period preceding the spring ice melting. In the river flow, using a stationary trawl, larvae were caught at equal intervals in the morning, afternoon and evening. The research period was 2 weeks (31.03.2023-14.04.2023). As a result of the research, it was established that there were 2 peaks of migration activity and density of burbot larvae in the periods 3.04-8.04 – the first and 10.04-12.04 – the second. The average density values in the specified periods were 0.066 and 0.034 ind./m3, with current speeds of 0.317 m/s and 0.450 m/s, respectively. The body length of the burbot larvae during the study period varied from 3.23 to 3.76 mm. Analysis of the dynamics during the migration period revealed a trend towards an increase in the body length of the larvae during the study period. Over the entire period of research, it was established that migration has a daily rhythm: it intensifies during the twilight period and slows down during the day.